Synthesis of 9-phosphonoalkyl and 9-phosphonoalkoxyalkyl purines: evaluation of their ability to act as inhibitors of Plasmodium falciparum, Plasmodium vivax and human hypoxanthine-guanine-(xanthine) phosphoribosyltransferases - Česnek, Michal; Hocková, Dana; Holý, Antonín; Dračínský, Martin; Baszczyňski, Ondřej; Jersey, John de; Keough, Dianne T; Guddat, Luke W (Bioorganic & medicinal chemistry, 2012)
The purine salvage enzyme, hypoxanthine-guanine-(xanthine) phosphoribosyltransferase [HG(X)PRT], catalyses the synthesis of the purine nucleoside monophosphates, IMP, GMP or XMP essential for DNA/RNA production. In protozoan parasites, such as Plasmodium, this is the only route available for their synthesis as they lack the de novo pathway which is present in human cells. Acyclic nucleoside phosphonates (ANPs), analogs of the purine nucleoside monophosphates, have been found to inhibit Plasmodium falciparum (Pf) HGXPRT and Plasmodium vivax (Pv) HGPRT with K(i) values as low as 100 nM. They arrest parasitemia in cell based assays with IC(50) values of the order of 1-10 μM. ANPs with phosphonoalkyl and phosphonoalkoxyalkyl moieties linking the purine base and phosphonate group were designed and synthesised to evaluate the influence of this linker on the potency and/or selectivity of the ANPs for the human and malarial enzymes. This data shows that variability in the linker, as well as the positioning of the oxygen in this linker, influences binding. The human enzyme binds the ANPs with K(i) values of 0.5 μM when the number of atoms in the linker was 5 or 6 atoms. However, the parasite enzymes have little affinity for such long chains unless oxygen is included in the three-position. In comparison, all three enzymes have little affinity for ANPs where the number of atoms linking the base and the phosphonate group is of the order of 2-3 atoms. The chemical nature of the purine base also effects the K(i) values. This data shows that both the linker and the purine base play an important role in the binding of the ANPs to these three enzymes.
Keywords: Pentosyltransferases; Antimalarials; Enzyme Activation; Plasmodium vivax; rekombinantní proteiny; Kinetics; Purines; Humans; aktivace enzymů; Plasmodium falciparum; lidé; Recombinant Proteins; pentosyltransferasy; antimalarika; protozoální proteiny; kinetika; puriny; Protozoan Proteins